A REPEATED CROSS-SECTIONAL MODEL FOR ANALYZING UNEMPLOYMENT DATA IN BOGOR - Ulfah Sulistyowati; Khairil Anwar Notodiputro; I Made Sumertajaya (Indonesian Journal of Statistics and Applications, 2020)
In general, the form of data encountered in statistical problems is panel data and cross-sectional data. There are times in certain conditions, the data formed in the form of a combination of panel data with cross-sectional data, which is commonly referred to as repeated cross-sectional data. Repeated cross-sectional data is often done in research with individual observations. In this study, a repeated cross-sectional analysis was carried out using a fixed influence model with observations in the form of an area (village) in Bogor, West Java to analyze unemployment factors. The results obtained are that ongoing village development affects the unemployment rate in Bogor